THE ESSAY ON APPLYING OF GEOINFORMATION TECHNOLOGY FOR CREATION OF GEOLOGICAL MONITORING SYSTEM IN KIEV AGGLOMERATION - VYZHVA, S.; KOSHLIAKOV, O.; KOZHAN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Major principles and approaches to creation of monitoring system of geological environment condition in Kiev agglomeration territory have been developed. Examples of the decision of hydro-geological and ecology-geophysical tasks on some parts have been resulted.